In Vivo Noninvasive Optical Imaging of Receptor-Mediated RGD Internalization Using Self-Quenched Cy5-Labeled RAFT-c(-RGDfK-) - Zhao-Hui Jin; Jesus Razkin; Veronique Josserand; Didier Boturyn; Alexeï Grichine; Isabelle Texier; Marie-Christine Favrot; Pascal Dumy; Jean-Luc Coll (Molecular Imaging, 2007)
We reported that regioselectively addressable functionalized template (RAFT)-c(-RGDfK-) 4 presenting four cyclic (Arg-Gly-Asp) (cRGD) peptides targets integrin a V b 3 with an improved specificity compared with monomeric cRGD. In this study, we improved this vector by creating a “stealth” molecule in which a fluorescence quencher (Q) is linked to Cy5 via a disulfide bond (-SS-). RAFT-c(-RGDfK-) 4 -Cy5-SS-Q fluorescence is quenched unless activated by reduction during internalization. RAFT-c(-RGDfK-) 4 -Cy5-SS-Q fluorescence was negligible when compared with the control but totally recovered after cleavage of the disulfide bridge. Confocal microscopy showed that only the intracellular Cy5 signal could be detected using RAFT-c(-RGDfK-) 4 -Cy5-SS-Q, confirming that uncleaved extracellular molecules are not visible. Whole-body imaging of mice bearing subcutaneous tumors injected intravenously with RAFT-c(-RGDfK-) 4 -Cy5-SS-Q showed a very significant enhancement of the fluorescent contrast in tumors compared with the unquenched molecule. Histology of the tumor confirmed the intracellular accumulation of Cy5. These results demonstrate that the presence of a labile disulfide bridge between the targeting vector and a drug mimetic is an efficient way to deliver a dye, or a drug, intracellularly. In addition, this quenched RAFT-c(-RGDfK-) 4 -Cy5-SS-Q probe is a very powerful vector for imaging tumor masses and investigating in vivo RGD-mediated internalization.